Association between Age at Type 2 Diabetes Onset and Diabetic Retinopathy: A Double-Center Retrospective Study - Mengdie Chen; Yiyun Wang; Ping Feng; Yao Liang; Qiao Liu; Mengyao Yang; Chaoyin Lu; Penghua Shi; Jian Cheng; Anjing Ji; Qidong Zheng (Journal of Diabetes Research)
Background. With the decreasing age of type 2 diabetes mellitus (T2DM) onset, the incidence of diabetic complications is gradually increasing. We evaluated the independent effect of age at diabetes onset on diabetic retinopathy (DR) development. Methods. A total of 7472 patients with T2DM were enrolled in the National Metabolic Management Center from September 2017 to May 2022. Anthropometry data, laboratory reports, and medical history were collected. The independent association of DR with age at diabetes onset was analyzed using multivariable logistic regression models. In addition, a stratified analysis was performed to determine the effect of confounding variables. Results. Of the 7472 patients recruited, 1642 (21.98%) had DR. Patients with DR had considerably younger ages of diabetes onset than those without DR (45 (38–53) years vs. 50 (43–57) years, P<0.001). The proportion of patients with T2DM onset at a younger age was higher in the DR group than that in the non-DR group. Participants were divided into four groups according to their age at diabetes onset, namely, ≥60, <40, 40–49, and 50–59 years. Compared with patients with diabetes onset at age≥60 years, those with diabetes onset at <40 years (odds ratio (OR): 5.56, 95% confidence interval (CI): 3.731–8.285, P<0.001), 40–49 years (OR: 2.751, 95% CI: 2.047–3.695, P<0.001), and 50–59 years (OR: 1.606, 95% CI: 1.263–2.042, P<0.001) were at an increased risk of DR after adjusting for potential confounding factors. Furthermore, stratification analyses demonstrated that young age at diabetes onset is an independent risk factor for DR. Conclusions. Compared with diabetes onset at an older age, diabetes onset at a younger age is associated with a significantly increased DR risk.